Cover Picture: A Twisted Nanographene Consisting of 96 Carbon Atoms (Angew. Chem. Int. Ed. 31/2017). Issue 31 (8th June 2017) - Cheung, Kwan Yin; Chan, Chi Kit; Liu, Zhifeng; Miao, Qian
Abstract : Three‐dimensional nanocarbon structures with negative curvature produced by embedding heptagons or octagons in the graphitic lattice have been proposed, but are yet to be synthesized. In their Communication onpage 9003 ff., Q. Miao et al. describe a new type of twisted nanographene, which can be regarded as a segment containing structural information of such negatively curved nanocarbon structures. Consisting of 96 sp 2 carbon atoms, this nanographene is twisted along two directions in the crystal.